Pharmacokinetics, toxicokinetics and safety margins - Rogge, Mark (Henry Stewart Talks, 2009)
The pharmacologic and toxic effects of a potential therapeutic agent are a consequence of the product concentration at the site of action, By understanding inter-species sensitivity to the agent and to the absorption and disposition properties, a rational first in human dose can be determined, Basic pharmacokinetic elements, Measures of exposure, Scaling methods and calculations of relative exposure, Utilizing outcomes from toxicology evaluations and associated exposure measures, First in human dose concept
Reviewed at 2019/02/26